Steel Packages 10 Years After Being Disposed as Litter in a Tropical Environment. Issue 2 (8th December 2015) - Santos, J. L. C.; Gatti, J. A. B.; Dantas, S. T.; Santos, W. R.
Abstract : A study considering Brazilian environmental conditions was carried out aiming to obtaining the development of data on the metal packaging performance when discarded in different natural conditions instead of an adequate disposal. The behaviour of steel packages in four local tropical environments during the time of 10 years was studied: on the ground at an industrial site, on the seashore, buried in the ground and immersed in a riverbed. Four different kinds of steel cans were used (plain powdered milk and soybean oil three piece tinplate cans and lacquered soft drink DWI tinplate can and tomato sauce tinplate three‐piece cans). Alternative packages containing the same products—PET bottles for soybean oil, DWI aluminium cans for soft drinks, laminated plastic bags for powdered milk and carton‐based multilayer packaging for tomato sauce—were used as control. Annually, samples of all packages were removed from the studied sites and visually analysed. Powdered milk and soybean oil cans were completely degraded in the industrial and marine environments between 6 and 7 years. Tomato sauce can sample was totally degraded between 7 and 8 years in the industrial environment. However, although some important surface damage was observed, none of the studied types of steel cans was completely degraded in both conditions: buried in the ground and immersed in a riverbed during the 10 years of study. Alternative packaging showed smaller alteration than steel cans in the studied period and conditions. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper presents the estimated average time for the degradation of steel packaging for soybean oil, soft drink, tomato products and powdered milk when disposed as litter in four tropical environments: (a) buried in the ground; (b) on the ground at an industrial site; (c) on the seashore; and (d) immersed in a riverbed. PET bottles, DWI aluminium cans, laminated plastic bags and carton based multilayer packaging were used as control.